The Effect of Work-Life Balance and Work Motivation on Employee Performance at Playtopia Tunjungan Plaza Surabaya - Fabio Aldhizyar; Moch. Arfani; Galuh Ajeng Ayuningtiyas (Asia Pacific Journal of Business Economics and Technology, 2026)
This study aims to analyze the effect of Work-Life Balance and Work Motivation on Employee Performance at Playtopia Tunjungan Plaza Surabaya. This research employed a quantitative approach with an explanatory research design. The population consisted of 15 employees of Playtopia Tunjungan Plaza Surabaya, and saturated sampling was used so that all 15 employees were included as respondents. Data were collected through questionnaires using a five-point Likert scale and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination using IBM SPSS Statistics. The results show that Work-Life Balance has a positive and significant effect on Employee Performance, with a significance value of 0.027 < 0.05. In contrast, Work Motivation does not have a significant effect on Employee Performance, with a significance value of 0.256 > 0.05. Simultaneously, Work-Life Balance and Work Motivation have a significant effect on Employee Performance, as indicated by an F-test significance value of 0.021 < 0.05. The coefficient of determination (R²) of 0.476 indicates that Work-Life Balance and Work Motivation jointly explain 47.6% of the variation in Employee Performance, while the remaining 52.4% is explained by other factors outside the research model. These findings indicate that Work-Life Balance plays a more significant role in explaining Employee Performance than Work Motivation when examined individually. Therefore, organizations should consider employees' work-life balance alongside motivational factors when developing strategies to improve employee performance.